Iatrogenic Lingual Neuralgia Following Laryngoscopy / Aziah Ab Rani and Sanjeevan Nadarajah - Ab Rani, Aziah; Nadarajah, Sanjeevan (Universiti Teknologi MARA Cawangan Selangor, 2018)
Tongue pain attributed to lingual neuralgia has been reported following dental and oral surgical procedures. Lingual nerve insult through traction and compression during laryngoscopic examination has been proposed as possible etiology for lingual nerve neuralgia. We report a case of tongue ischemia during laryngoscopic procedure which resulted in lingual neuralgia. We recommend that intermittent release of pressure by relaxing the instrument or gag and monitoring the perfusion state of the tongue will reduce the risk of this lingual neuralgia.